Usefulness of the CLLflow score. Issue 6 (19th January 2018) - Sorigue, Marc; Franch‐Sarto, Mireia; Sarrate, Edurne; Junca, Jordi
Abstract : Background: The CLLflow score was recently suggested as an improvement over the Moreau score (MS) for the diagnosis and classification of B‐cell lymphoproliferative disorders (B‐LPD). Methods: We determined the CLLflow score in peripheral blood or bone marrow of a series of cases with an inconclusive immunophenotype, including samples with a MS of 3 ( n  = 52) and CD5‐positive with a score of 2 ( n  = 38). As controls, B‐LPD with a MS of 0–1 ( n  = 95), CD5‐negative score 2 ( n  = 24), and score 4–5 (i.e., chronic lymphocytic leukemia [CLL], n  = 166) were included. Results: The CLLflow score was positive (suggestive of CLL) in all CLL cases and negative in all MS <2, regardless of CD200‐positivity, which occurred in 31% (29/95) of cases. The CLLflow score was positive in 71%, 29%, and 8% of samples with a MS 3, CD5‐positive score 2, and CD5‐negative score 2, respectively. Discussion: Our results suggest that the CLLflow is useful in the differential diagnosis of cases with inconclusive immunophenotype. © 2018 International Clinical Cytometry Society